Research on Brand Construction and Marketing of Wahaha Group in China - Weijie, Zhao; Yudiaatmaja, Fridayana (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
Brand construction and marketing are crucial for a company's success, particularly in highly competitive industries such as the Chinese beverage sector. Wahaha Group, a leading Chinese beverage company, has established a strong market presence through strategic brand-building efforts and innovative marketing approaches. This study examines the brand construction and marketing strategies of Wahaha, exploring how digital transformation, consumer engagement, and sustainability practices contribute to brand equity and competitive advantage. The research is grounded in Consumer Culture Theory (CCT), Integrated Marketing Communications (IMC) Theory, and Diffusion of Innovation Theory, providing a theoretical framework to analyse Wahaha’s marketing strategies and their impact on consumer behaviour. The study highlights Wahaha’s integration of traditional and digital marketing techniques, including celebrity endorsements, e-commerce expansion, and social media engagement, which have significantly enhanced brand recognition and customer loyalty. However, challenges such as increasing consumer awareness of sustainability, inflationary pressures, and regulatory constraints pose risks to its market position. By leveraging digital marketing, expanding product diversification, and strengthening its sustainability commitments, Wahaha can navigate the evolving business landscape and maintain its competitive edge. This study provides insights into the dynamic interplay between brand construction, market strategies, and consumer behaviour, offering practical recommendations for businesses seeking to strengthen their market position in China’s evolving economic environment.